Addressing communication barriers for autistic students in inclusive education from teachers’ perspectives - Utami, Ima Hidayati; Riani, Yuyun Agus (Universitas Padjadjaran, 2026)
Background: In inclusive education, communication between teachers and students with autism spectrum disorder (ASD) is framed as an individual deficit, obscuring the relational, emotional, and contextual conditions through which understanding is produced or disrupted. Purpose: This study reframes communication barriers as relational and situational challenges, which teachers negotiate in their lived experiences. Methods: A qualitative phenomenological–interpretive approach was used to gather data through reflective written accounts from 18 teachers of ASD-inclusive classrooms, which were thematically analyzed. Results: The results suggest that communication barriers are dynamic, interactional, and emotionally mediated. Teachers reported breakdowns in the domains of emotional dysregulation and sensory and environmental overload, as well as mismatches between classroom expectations and students’ pragmatic repertoires. They relied on real-time adaptation, emotional attunement, visual scaffolds, and augmentative and alternative communications (AAC) in response. These practices correlated with greater trust, less spiral-down dynamics, better regulation, and more student-initiated engagement, while making visible teachers’ agency despite limited training and institutional support. Thus, the success of communication in ASD-inclusive education can be understood as a dialogic, ethical, embodied, and culturally situated practice that cultivates trust, emotional safety, mutual understanding, and teachers’ professional transformation. Implications: The study calls for education policies and professional development to address relational competence, reflective practice, and the provision of sustained structural support in communication.